Quality of life in patients with chronic vulvovaginal candidiasis: A before and after study on the impact of oral fluconazole therapy. (11th May 2016) - Nguyen, Yvonne; Lee, Andrew; Fischer, Gayle
Abstract: Background/Objective: Chronic vulvovaginal candidiasis (CVVC) is a disorder characterised by the signs and symptoms of vulvovaginal inflammation and causally associated with the presence of Candida spp. in the vagina. This study aimed to establish the impact of treatment with fluconazole in CVVC on patients' quality of life (QoL). Methods: This was a before and after study conducted in vulval dermatology clinics in Sydney, Australia. Patients were assessed at baseline by the dermatology life quality index (DLQI) and visual analogue scale (VAS) grading of erythema at baseline and at 12 weeks after an oral fluconazole regime. The primary outcome measures were a change in their DLQI score and VAS grading. The secondary outcome measures were its tolerability and adverse events. Results: A total of 82 of 91 patients (90%) completed the study. The mean drop in their DLQI score was 11.6 [95% CI (10.1, 13.0)] ( P < 0.001). The post‐treatment VAS scores were significantly lower than the pretreatment scores ( P < 0.001). Adverse effects requiring cessation of fluconazole occurred in 4% of patients. Conclusions: Fluconazole treatment at a dose of 50–100 mg daily achieved a significant observable and improvement in the QoL of 96% of patients with CVVC within 12 weeks of treatment. Adverse effects were minimal.